SURGICAL MANAGEMENT OF VAGINAL AGENESIS IN MAYER–ROKITANSKY–KÜSTER–HAUSER SYNDROME: MULTI-CENTER EXPERIENCE - Aisha Nazeer; Sana Urooj; Usman Ali Faisal; Sohail Hameed; Muhammad Usman Hafeez; Waleed Abdullah (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Mayer–Rokitansky–Küster–Hauser (MRKH) syndrome is a rare congenital anomaly characterized by agenesis or hypoplasia of the uterus and upper two-thirds of the vagina, resulting in primary amenorrhea and profound implications for sexual and reproductive health. Vaginal reconstruction in these patients represents a complex surgical challenge requiring specialized expertise.Aims & Objectives: This multicenter retrospective study aimed to evaluate the clinical outcomes and surgical efficacy of neovaginal reconstruction using the Abbe–McIndoe technique in patients with MRKH syndrome across major urban centers in Pakistan.Methodology: A retrospective analysis was conducted on 78 patients diagnosed with MRKH syndrome who underwent neovaginal reconstruction from January 2024 to April 2025. Data were collected from tertiary care surgery and gynecology departments located in Karachi, Lahore, Islamabad, Rawalpindi, Faisalabad, and other large metropolitan areas. Patients were selected through a non-probability convenience sampling technique. All participants had confirmed 46, XX karyotype and were diagnosed via clinical and imaging assessments by certified gynecologists. Surgical reconstruction was performed using the standardized Abbe–McIndoe technique, employing split-thickness autologous skin grafts. Perioperative, intraoperative, and long-term postoperative outcomes were systematically recorded and analyzed.Results & Findings: The mean age of participants was 21.4 years (range: 15–32 years). All patients exhibited a normal female karyotype (46, XX) with absence of the uterus and proximal vagina, and normal development of secondary sexual characteristics. The mean operative time was 3.1 ± 0.5 hours. The average neovaginal length achieved postoperatively was 10.7 ± 1.1 cm. Early complications included rectovaginal fistula in 2 patients (2.6%) and superficial graft necrosis in 4 patients (5.1%), all managed by surgeons. At six-month follow-up, 89.7% of patients reported satisfactory anatomical and functional outcomes, with 82% achieving regular and pain-free sexual intercourse. No cases of graft rejection or severe infections were documented.Conclusion: The Abbe–McIndoe technique remains a reliable and effective surgical modality for neovaginal construction in patients with MRKH syndrome, particularly in resource-limited settings. The results from this large multicenter Pakistani cohort reinforce the safety and functional efficacy of this technique when performed in specialized centers. However, there is an urgent need for increased awareness, surgeon training, and multidisciplinary collaboration to address the unmet surgical needs of MRKH patients in developing countries.